Acute and chronic effects of training with a fixed gear on pedaling technique - Fernández-Peña, E.; Benelli, P.; Bertuccioli, A.; Patti, A.; Gervasi, M. (Journal of Science and Cycling, 2023)
In cycling, the round pedaling technique is characterized by applying force as uniformly as possible throughout the entire pedal cycle (2). This involves applying more force in areas of the pedal stroke such as dead spots or the recovery phase. Although there is still controversy as to which type of pedaling technique is more metabolically efficient (1, 8), the round pedaling reduces the load on the most important muscles for propulsion in cycling, i.e. the knee extensors (3). In this way, the work necessary to maintain the intensity of the exercise is distributed among other leg muscles (3), which would translate into a greater potential to use the knee extensors in the crucial moments of the competition.